Attachment to parents and anxiety in young adults - Silva, Maria da Graça (2004)
The main goal of this study was the analysis of the relationship between attachment to parents style, based in Bartholomew & Horowitz (1991) and anxiety in young adults. The present research was developed in a sample of 511 portuguese youngsters, with ages between 17 and 26 years, which attended several higher education courses in the Porto area. In general, we have found significant low correlations between the quality of bonding and exploration and individuation inhibition to mother and father and fears and obsessive-compulsive characteristics. We also have foundsignificant low positive correlations or moderately low correlations between the separation anxiety and dependency to mother and father and anxiety. With respect to attachment style, we have registered significant effects in the different kinds of fear and in the obsessive thoughts and compulsive behaviors: subjects with insecure attachment style have presented higher means in most of the fears and obsessive-compulsive characteristics. We discuss implications of results to psychological development, specifically a more positive view of themselves and of the others and to prevent anxiety structuration as well. DOI: http://dx.doi.org/10.17575/rpsicol.v18i2.428